2015
DOI: 10.1002/cssc.201501082
|View full text |Cite
|
Sign up to set email alerts
|

Charge Modulation in Graphitic Carbon Nitride as a Switchable Approach to High‐Capacity Hydrogen Storage

Abstract: Electrical charging of graphitic carbon nitride nanosheets (g-C4 N3 and g-C3 N4 ) is proposed as a strategy for high-capacity and electrocatalytically switchable hydrogen storage. Using first-principle calculations, we found that the adsorption energy of H2 molecules on graphitic carbon nitride nanosheets is dramatically enhanced by injecting extra electrons into the adsorbent. At full hydrogen coverage, the negatively charged graphitic carbon nitride achieves storage capacities up to 6-7 wt %. In contrast to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…% at full loading. 42 Despite the promising possibilities demonstrated in the calculations, the present issues confronting efforts to experimentally verify the findings with these materials are that g-C 4 N 3 is not yet readily synthesized in useful quantities, while g-C 3 N 4 is a semiconductor with bandgap calculated to be just under 2 eV, meaning that it will not display good conductivity as needed for the charging process.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…% at full loading. 42 Despite the promising possibilities demonstrated in the calculations, the present issues confronting efforts to experimentally verify the findings with these materials are that g-C 4 N 3 is not yet readily synthesized in useful quantities, while g-C 3 N 4 is a semiconductor with bandgap calculated to be just under 2 eV, meaning that it will not display good conductivity as needed for the charging process.…”
mentioning
confidence: 99%
“…This can be immensely frustrating for all sorts of reasons, but every so often a powerful new discovery reinforces one's confidence that the effort is worth it in spades! In this contribution, following a preliminary body of work, 18,22,25,26,36,37,41,42,48 we have taken a step back to consider some underlying trends that dictate electrocatalytic CO 2 binding in a group of 1:1 X-N graphene analogue materials. The results indicated that the electro-responsive switching behavior correlates with a change in the preferred CO 2 binding site from N to the adjacent X atom as more negative charge is introduced into the system.…”
mentioning
confidence: 99%
“…However, the electric field strength in this study is around 23000 MVm -1 , which was too large for experimental realization. On the other hand, researchers also found that when extra charges were injected into adsorbents, the gas adsorption capacity of this adsorbents could be extremely enhanced [17][18][19][20][21]. Notably, the kinetics of gas adsorption and release could be modulated by tuning charge density, yielding a controlled adsorption and desorption process.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the kinetics of gas adsorption and release could be modulated by tuning charge density, yielding a controlled adsorption and desorption process. Until now, various materials have been developed and explored for charge-controlled H2 storage [17][18][19][20][21]. B-doped graphene has been proposed as an excellent charge-modulated H2 storage material.…”
Section: Introductionmentioning
confidence: 99%
“…Charging of electrocatalytic materials can be an efficient method for modifying or modulating molecular interactions and reactivity at heterogeneous interfaces, including gas capture and separation processes and electrochemical and electrocatalytic reactions. Heterogeneous charge-responsive molecular binding to electrocatalytic materials has been predicted in several recent works. For instance, density functional theory (DFT) calculations have revealed that gas phase CO 2 molecules undergo weak physisorption (through van der Waals interactions) on hexagonal boron nitride ( h -BN) in the absence of charging.…”
Section: Introductionmentioning
confidence: 99%